2020
DOI: 10.1002/cpt.1790
|View full text |Cite
|
Sign up to set email alerts
|

“In‐House” Data on the Outside—A Mobile Health Approach

Abstract: Mobile health (mHealth) technologies have the potential to capture dense patient data on the background of real‐life behavior. Merck & Co., Inc. (Kenilworth, NJ), in collaboration with Koneksa Health, conducted a phase I clinical trial to validate cardiovascular mHealth technologies for concordance with traditional approaches and to establish sensitivity to detect effects of pharmacological intervention. This two‐part study enrolled 18 healthy male subjects. Part I, a 5‐day study, compared mHealth measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…73,75,76 Merck & Co., Inc. (Kenilworth, NJ, USA) also conducted a study in collaboration with Koneksa Health that explored use of mobile health approaches to measure changes in heart rate and blood pressure, which found that mobile health approaches were comparable to standard in-clinic measures and Accepted Article sufficiently sensitive to detect treatment differences, demonstrating potential to capture rich hemodynamic data in early clinical trials to aid decision-making. 77 Digital biomarkers may be particularly useful in disease areas that are hindered by a lack of validated biomarkers to objectively measure disease onset and progression, such as neurodegenerative diseases.…”
Section: Accepted Articlementioning
confidence: 99%
See 4 more Smart Citations
“…73,75,76 Merck & Co., Inc. (Kenilworth, NJ, USA) also conducted a study in collaboration with Koneksa Health that explored use of mobile health approaches to measure changes in heart rate and blood pressure, which found that mobile health approaches were comparable to standard in-clinic measures and Accepted Article sufficiently sensitive to detect treatment differences, demonstrating potential to capture rich hemodynamic data in early clinical trials to aid decision-making. 77 Digital biomarkers may be particularly useful in disease areas that are hindered by a lack of validated biomarkers to objectively measure disease onset and progression, such as neurodegenerative diseases.…”
Section: Accepted Articlementioning
confidence: 99%
“…This article is protected by copyright. All rights reserved There are several platform providers that offer such capabilities 77,91,92 , and we have tested several of these capabilities from various providers and are introducing these approaches into trials dependent on study need.…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations